Obowiązkowe ubezpieczenie odpowiedzialności cywilnej organizatora meczu piłki nożnej za szkody wyrządzone w czasie jego trwania - Stefanicki, Robert; Wójtowicz, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The Act on Mass Events Security of 20 March 2009 sets out in Article 53 the compulsory civil liability insurance of the organizer of mass events against payments — including football matches — for damages suffered by participants caused by acts or omissions of the insured party. Regulation of Minister of Finance on the mandatory civil liability insurance of the organizers of mass events of 11 March 2010 regulates in details the mandatory insurance coverage, specifies the date of the obligation and prescribes minimum insurance amounts. The aim of the compulsory civil liability insurance is to create the necessary guarantees for the protection of the victims and to protect the victims against the possible insolvency of the person liable for the occurrence of damage who is obliged to cover the damage suffered.
Keywords: impreza masowa; organizator imprezy masowej; obowiązkowe ubezpieczenie odpowiedzialności cywilnej